Cultural history of Telangana : from the earliest times to 1724AD - Bhukya, Bhangya (Hyderabad Orient Blackswan, 2021)
Telangana, with its rocky terrain, thick forests, hilly landscapes and red sandy soils, has produced a diverse social, economic and political system. This diversity has led to intense cultural assimilation over the centuries, producing a new culture known as Deccani. A Cultural History of Telangana takes a longue durée approach to understanding the socio-economic, cultural and political movements in the region, delineating the broad trends and themes in Telangana s history. Moving away from the dynastic perspective commonly deployed in conventional history writing, the author follows significant developments in the fields of agriculture, urbanisation, architecture, trade and commerce, religion, and the arts to reconstruct the unique history of Telangana from ancient times up to the early eighteenth century.
Keywords: Cultural History; Telangana